GREEN KNOWLEDGE RELIGIUSITAS DAN KEPUTUSAN PEMBELIAN GREEN PRODUCT PADA KONSUMEN MUSLIM GENERASI Z - Umamatul Faizah; Rafidah Rafidah; Aztyara Ismadharliani (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This study aims to determine and analyze the effect of green knowledge and religiosity on purchasing decisions of green products among Muslim consumers of the Z generation of students of the Faculty of Economics and Islamic Business, Sulthan Thaha Saifuddin State Islamic University, Jambi. This research is a quantitative type. The sample used was 91 respondents. The analysis used in this study is validity test, reliability test, multiple regression analysis, T test, F test and analysis of the coefficient of determination. The research was carried out using multiple linear regression equations for the effect of green knowledge and religiosity is Y = -0.521 + 0.729 X1 + 0.234 X2 + e. The influence of green knowledge and religiosity together have a significant and positive effect on green product purchasing decisions because the results of the F test carried out yielded Fcount > Ftable or 105.347 > 3.10 with a significance value of 0.000 > significant level of 0.05. The coefficient of determination is 0.699, which means that the influence of green knowledge and religiosity together influence the purchase decision of R2, namely 69.9%, while the remaining 30.1% is influenced by other factors.